2020
DOI: 10.1159/000506071
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cariporide in Protecting Saphenous Vein among Different Aldehyde Dehydrogenase Genotypes

Abstract: Objective: We aimed to study the effect of cariporide (CP) on protecting the saphenous vein and the role of acetaldehyde dehydrogenase 2 (ALDH2) in coronary artery bypass grafting (CABG). Background: The saphenous vein is the main graft material used in CABG. Recent studies suggested that CP is effective in protecting against various cardiovascular diseases. Methods: Segments of a surgically removed saphenous vein were used to examine the vascular response to CP. The ALDH2 genotype and expression of related pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, cariporide failed in phase 3 clinical trials for CAD patients due to increased mortality ( 75 ). More recently, one study showed that cariporide could improve vascular function ex vivo in saphenous veins from ALDH2*2 carriers ( 76 ), suggesting that NHE-1 may be a potential therapeutic target for follow-up studies in either specific patient populations or with other small molecules.…”
Section: Discussionmentioning
confidence: 99%
“…However, cariporide failed in phase 3 clinical trials for CAD patients due to increased mortality ( 75 ). More recently, one study showed that cariporide could improve vascular function ex vivo in saphenous veins from ALDH2*2 carriers ( 76 ), suggesting that NHE-1 may be a potential therapeutic target for follow-up studies in either specific patient populations or with other small molecules.…”
Section: Discussionmentioning
confidence: 99%